Living Mushaf: Penelusuran atas Sakralitas Penggunaan Mushaf dalam Keseharian - Eva Nugraha (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2013)
The text of the Qur’ān which is manifested in the form of mushaf has existed just only in the post- codification of ‘Uthmān ibn ‘Affān. Nevertheless, in fact, not all mufassirs agree that the word al-Qur’ān Karīm (Q.s. 56: 77-79) is a synonym for the word mushaf that is used today; therefore mushaf must be purified and sacralized. Based on the mentioned reason, this paper will study why Muslims give sanctity to the use of the mushaf in their daily lives. The answer for the question is constructed in two questions. First, how sanctification and sacralization of mushaf happen?, and is the expression of the Muslims today is a form of cultural sacralization of mushaf? This writing mostly uses library data which is combined with linguistic, history and cultural approaches.